2022
DOI: 10.1038/s41420-022-01157-4
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA in tumorigenesis of non-small-cell lung cancer: From bench to bedside

Abstract: Lung cancer has been one of the leading causes of cancer-related death worldwide, and non-small-cell lung cancer (NSCLC) accounts for the majority of lung cancer morbidity, yet the pathogenesis of NSCLC has not been fully elucidated. Recently, long-chain non-coding RNA (lncRNA) has attracted widespread attention. LncRNA is a type of non-coding RNA whose transcript length exceeds 200 nucleotides. After constant research, academics updated their understanding of lncRNA, especially its role in the biological proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 64 publications
0
26
0
Order By: Relevance
“…Recent studies demonstrated that some transcripts that are annotated as lncRNAs actually encode for small proteins and that lncRNAs can be processed into small ncRNAs such as miRNAs or piRNAs [ 198 , 199 , 200 ]. LncRNAs can exert oncogenic or tumor suppressor functions affecting different biological processes such as cell proliferation, cell death and drug resistance [ 201 , 202 , 203 ]. LncRNAs can be secreted into the circulation system via exosomes or bound to RBPs.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Recent studies demonstrated that some transcripts that are annotated as lncRNAs actually encode for small proteins and that lncRNAs can be processed into small ncRNAs such as miRNAs or piRNAs [ 198 , 199 , 200 ]. LncRNAs can exert oncogenic or tumor suppressor functions affecting different biological processes such as cell proliferation, cell death and drug resistance [ 201 , 202 , 203 ]. LncRNAs can be secreted into the circulation system via exosomes or bound to RBPs.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…LncRNA is non-coding RNA with a length >200 bp, which is a major regulator of gene expression [212]. LncRNA can interact with miRNA and affect the proliferation, invasion and metastasis of NSCLC cells [218]. LncRNA XLOC_008466 is highly expressed in patients with NSCLC and binds to miR-874 to down-regulate its level and increase miR-874 downstream target expression to promote cancer cell proliferation and invasion [219].…”
Section: Non-coding Rnamentioning
confidence: 99%
“…Non-coding RNAs have been reported to involved in human cancer development and progression ( Ghafouri-Fard et al, 2020 ; Yan and Bu, 2021 ; Chen T. et al, 2022 ; Liu and Shang, 2022 ). Evidence has shown that lncRNAs play an essential role in NSCLC initiation, development and progression ( Osielska and Jagodzinski, 2018 ; Wang et al, 2018 ; Hu et al, 2022 ). Moreover, non-coding RNAs are critically involved in cancer drug resistance in human cancers ( Jiang et al, 2020 ; Zhou X. et al, 2022 ; Xie et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%